2019
DOI: 10.1080/21505594.2019.1599669
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transcriptomes of Streptococcus suis reveal genes required for niche-specific adaptation and pathogenesis

Abstract: Streptococcus suis is a Gram-positive bacterium and a zoonotic pathogen residing in the nasopharynx or the gastrointestinal tract of pigs with a potential of causing life-threatening invasive disease. It is endemic in the porcine production industry worldwide, and it is also an emerging human pathogen. After invasion, the pathogen adapts to cause bacteremia and disseminates to different organs including the brain. To gain insights in this process, we infected piglets with a highly virulent strain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…Our results clearly showed that PmtA does not affect the virulence of S. suis in mice. Consistent with this result, Arenas et al recently demonstrated that pmtA (SSU0288) is downregulated at all sites of infection and plays no major role in S. suis survival within the host using the piglet infection model [45]. Based on these observations, it is conceivable that the host may not employ iron toxicity to control bacterial infections.…”
Section: Discussionmentioning
confidence: 76%
“…Our results clearly showed that PmtA does not affect the virulence of S. suis in mice. Consistent with this result, Arenas et al recently demonstrated that pmtA (SSU0288) is downregulated at all sites of infection and plays no major role in S. suis survival within the host using the piglet infection model [45]. Based on these observations, it is conceivable that the host may not employ iron toxicity to control bacterial infections.…”
Section: Discussionmentioning
confidence: 76%
“…Based on these results, we conclude that S. suis uses a balanced network of regulators to control metabolic adaptation and stress responses during infection. In our previous work, we showed that metabolic adaptation of S. suis to the different sites of infection is causing large changes in gene expression [21]. In this study, it is shown that these metabolic changes are not facultative, but essential for S. suis in order to survive in the harsh conditions of the host.…”
Section: Transcription Regulationmentioning
confidence: 65%
“…At the start of the experiment tonsil swabs of piglets were screened for the absence of S. suis serotype 2 isolates. After an acclimatization period of 3 days, piglets were infected intravenously with 10 6 CFU of strain 10 and coinfected with the same amount of one of the isogenic mutants as previously described [21]. After infection, blood was extracted at a daily base to allow white blood cell counting, and piglets were observed for clinical symptoms and behavior three times a day at 8 h intervals.…”
Section: Co-infection Experimentsmentioning
confidence: 99%
“…There may be a second methionine uptake system similar to the BcaP system of Lactococcus lactis to obtain methionine from the environment (den Hengst et al 2006 ; Basavanna et al 2013 ). Methionine synthesis and transport genes were reported to be related to the virulence of Brucella melitensis , Salmonella enterica and Streptococcus suis (Lestrate et al 2000 ; Ejim et al 2004 ; Arenas et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%